Green water efficiency in the vulnerable silk road economic belt - Zhang, Qiang; Long, Hai (Frontiers in Environmental Science, 2023)
Introduction: In vulnerable environments, accurate and complete assessments of green water efficiency (GWE) must consider unexpected outputs. Methods: This study employed the hyper-efficiency SBM-DEA model and SDM method to investigate the spatial heterogeneity and the determinants of GWE, respectively, in nine Chinese provinces along the Silk Road Economic Belt (SREB), which is characterized by a vulnerable ecological and economic system. Results: Using data from 2008 to 2019, this study found that the green performance indicator varied in these provinces; GWE showed substantial spatial heterogeneity, with a negative spatial autocorrelation among the provinces with a low-to-high or high-to-low distribution. The southwest provinces had a higher GWE than the northwest, but there was no significant GWE improvement in the whole region. Both governmental engagement and environmental protection were the most influential determinants of GWE, which showed spatial spillover effects, followed by water pollution then economic growth, demonstrating that the GWE in vulnerable ecosystems may be changed by any factor depending on unexpected outputs. Discussion: This study suggests that reducing the side effects of unexpected outputs in vulnerable environments, because the ecosystem will be redamaged by unexpected contaminants when improving the local GWE.